Saturation Dependence of Flame Thermometry Using Mid-IR Degenerate Four Wave Mixing. Issue 1 (January 2021) - Pedersen, Rasmus L.; Sahlberg, Anna-Lena; Hot, Dina; Li, Zhongshan
It has previously been demonstrated that the ratio of the degenerate four wave mixing signal from two hot water line groups near 3231 cm –1 can be used for seedless flame temperature measurements. This paper presents an investigation of the impact of saturation effects on the measured signal intensity from each line group, as well as an estimation of the accuracy of the method. The saturation effects observed here would result in a large systematic error if they are not taken into account when using the degenerate four-wave mixing intensity of these water line groups to calculate the flame temperature.